0
$\begingroup$

I have $x(t)$ and $t$, to rescale and ODE, I need to perform a change of variable $x = \alpha x_s$ and $t = \beta t_s$

I was told that the derivative $\frac{dx}{dt} = \frac{dx}{dx_s}\frac{dx_s}{dt_s}\frac{dt_s}{dt} $ which then equals $ \frac{\alpha}{\beta}\frac{dx_s}{dt_s}$ due to chain rule But I'm having trouble understanding how chain rule works when $t$ is also a function of something else.

I'm also trying to find a expression for $\frac{d^2x}{dt^2}$

$\endgroup$
0
$\begingroup$

If t is a function of something else we need to consider what we are differentiating with respect to. That is, of course the derivative of $t$ with respect to itself ($dt/dt$) is one. But now, look at $t=\beta t_s$. We treat $t$ as a function of $t_s$, so $\frac{dt}{dt_s}=\beta\frac{dt_s}{dt_s} =\beta$. Next, look at $x=\alpha x_s$. One thing to note, that is when we do this change in variable, we are actually saying $x(t)=\alpha x_s(t_s)$ where $t=\beta t_s$. So $\frac{dx}{dt}=\frac{d}{dt}[\alpha x_s(t_s)]=\alpha\frac{d}{dt}x_s(t_s)$. Now, we need to look at $\frac{d}{dt}x_s(t_s)$. This is the main part of chain rule. $x_s$ is a function of $t_s$, so $\frac{d}{dt}x_s$ is kind of off. Chain rule tells us that if $y=f(u)$ and $u=g(x)$ then $\frac{df}{dx}=\frac{df}{du}\frac{du}{dx}$. So, in our case, $\frac{d}{dt}x_s=\frac{dx_s}{dt_s}\frac{dt_s}{dt}$. And $\frac{dt_s}{dt}=1/\beta$. Which putting all together gives the result. Now we have that $\frac{dx}{dt}=\frac{\alpha}{\beta}\frac{dx_s}{dt_s}.$ For the 2nd derivative, its similar. We want to find $\frac{d}{dt}(\frac{\alpha}{\beta}\frac{dx_s}{dt_s})$, but $\frac{\alpha}{\beta}\frac{dx_s}{dt_s}$ is now the function that depends on $t_s$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.